2010
DOI: 10.1177/1073191110386342
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Factor Structure and Concurrent Validity of the Langer Mindfulness/Mindlessness Scale

Abstract: Langer's theory of mindfulness proposes that a mindful person seeks out and produces novelty, is attentive to context, and is flexible in thought and behavior. In three independent studies, the factor structure of the Langer Mindfulness/Mindlessness Scale was examined. Confirmatory factor analysis failed to replicate the four-factor model and a subsequent exploratory factor analysis revealed the presence of a two-factor (mindfulness and mindlessness) solution. Study 2 demonstrated that the two factors assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 30 publications
6
57
0
6
Order By: Relevance
“…The aim of this longitudinal cohort study of 125 patients with severe TBI and controls was validation of the Langer Mindfulness Scale [36,43] in German. The results of the factor analysis and the response theory analysis indicated that the 21-item scale could be reduced to a 6-item scale for the German version, with minimal loss of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this longitudinal cohort study of 125 patients with severe TBI and controls was validation of the Langer Mindfulness Scale [36,43] in German. The results of the factor analysis and the response theory analysis indicated that the 21-item scale could be reduced to a 6-item scale for the German version, with minimal loss of information.…”
Section: Discussionmentioning
confidence: 99%
“…Langer's approach to mindfulness has been studied mostly among healthy samples thus far, yielding significant improvement in areas of life satisfaction, creativity, as well as mental and physical well-being [41,43]. Despite its importance, the exploration of mindfulness in samples of people with TBI is currently limited by the lack of validated instruments for measuring mindfulness as a trait.…”
Section: Introductionmentioning
confidence: 99%
“…More evidence in favor of this hypothesis has been published recently. Haigh et al [44] reported, in a study related to the construction of the Langer Mindfulness/Mindlessness Scale that they were able to detect both a mindfulness and a mindlessness factor. Future research should consider that -mindfulness questionnaires‖ and -mindlessness questionnaires‖ may not assess the same latent construct.…”
Section: Discussionmentioning
confidence: 99%
“…The Langer Mindfulness Scale (LMS) was used to determine each participant's relative level of personal mindfulness. The LMS is a 21-question survey proven to be an accurate measure of relatively stable trait mindfulness (Bodner and Langer, 2001;Haigh et al, 2011). Recent efforts to refine the scale (Pirson et al, 2012) found further accuracy using a shortened 14-item version.…”
Section: Materials and Measuresmentioning
confidence: 99%